Layanan Konseling Behavioral dengan Teknik Self-Management di Rumah Pelayanan Sosial Anak Pamardi Siwi Sragen - Ardian Kusuma Putra; Alfin Miftahul Khairi (Transformatif : Jurnal Pengabdian Masyarakat, 2020)
Adolescence is a childhood full of play that enters the age of maturity and requires maximum responsibility. During this period, there is an emotional upgrowth that is accompanied by a growing physical and psychic. Therefore, emotional intelligence is needed for teenagers, one of which is in the Pamardi Siwi Sragen Child social Service house. The purpose of this community servicesis to know the process of behavioral counseling with self management techniques to overcome low emotional intelligence in orphans in adolescent youth at the Pamardi Siwi Sragen Child social Service house. The process of behavioral counseling with self management techniques at the Pamardi Siwi Sragen Children's social service house, there are stages of behavioral counseling with self management techniques such as assesment, treatment In the form of motivation and implementation of self management techniques, and the last entered into the CC (case conference) stage. But there is inconsistency between the process of implementing self management techniques in the field with the theory used by researchers.